Fiber bragg grating based ph sensor - Yulianti, Ian (American Institute of Physics, 2011)
This paper demonstrates the modeling of pH sensor based on pH sensitive hydrogel coated FBG. The modeling was done by simulating the hydrogel swelling behavior, then calculating the strain induced by hydrogel expansion. Meshless numerical method was adopted to solve the Poison Nernst Planck equation coupled to mechanical equation to simulate the hydrogel swelling. The strain induced in the FBG due to mechanical expansion of hydrogel was calculated analytically. Strain of more than 10 mue was obtained at pH> 5. At pH of 5, lambdaB shift of more than 10 pm was achieved.